Numerical modelling of mode-I cracking in asphalt concrete - Ahmed Awais; Khan Rawid (E3S Web of Conferences, 2022)
This paper presents a numerical model to simulate mode-I fracture in asphalt concrete. The phase field method is used to simulate diffuse damage in asphalt concrete. In addition to the displacement degrees of freedom, a scalar damage degree of freedom is added at each node of a finite element. Evolution of the damage variable is governed by a crack potential which regularizes a sharp crack over a finite volume. The phase field method does not suffer from mesh dependency problem like the continuum damage models and therefore preferred for damage analysis. A single edge notch beam is analysed to show the performance of the model. The damage pattern as well as load versus crack mouth opening displacement graph is compared with the experimental data. The numerical results show good agreement with the experimental observations.